1991
DOI: 10.1093/ndt/6.6.420
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hypertension by Yerapamil Enhances Renal Damage in a Rat Remnant Kidney Model

Abstract: Abstract. The effect of calcium channel blockers on the progression of renal failure is controversial. In contrast with earlier studies, we recently reported that moderately large doses of verapamil significantly accelerated chronic renal failure in the rat remnant kidney model [1]. Studies reporting beneficial effects of verapamil were characterised by a much lower dose of verapamil and by the start of treatment immediately after renal ablation, which potentially interfered with the initial phase of remnant k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Brunner et al studied the effects of different dosages of verapamil in the rat remnant kidney model, and found that an intermediate dose resulted in minor effects on blood pressure, more proteinuria and more glomerulosclerosis. The higher dose, which lowered blood pressure more effectively, did not significantly increase proteinuria nor glomerulosclerosis [46,47]. Dworkin used both nifedipine and amlodipine in the uninephrectomized DOCA-salt rat model and in the uninephrectomized spontaneously hypertensive rat (SHR) rat [27,28,53].…”
Section: Role Of Glomerular Capillary Pressure and Renal Autoregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brunner et al studied the effects of different dosages of verapamil in the rat remnant kidney model, and found that an intermediate dose resulted in minor effects on blood pressure, more proteinuria and more glomerulosclerosis. The higher dose, which lowered blood pressure more effectively, did not significantly increase proteinuria nor glomerulosclerosis [46,47]. Dworkin used both nifedipine and amlodipine in the uninephrectomized DOCA-salt rat model and in the uninephrectomized spontaneously hypertensive rat (SHR) rat [27,28,53].…”
Section: Role Of Glomerular Capillary Pressure and Renal Autoregulationmentioning
confidence: 99%
“…One factor that may explain the differences in outcome of the various studies is the interval between the induction of injury and the start of the treatment. In most studies in Table 1 (the protective studies) treatment was started immediately after induction of the injury, whereas in the negative studies the start of treatment was often delayed [46,47,51,52]. The importance of the timing of the start of treatment is highlighted by the studies of Dworkin.…”
Section: Role Of Timing Of Treatmentmentioning
confidence: 99%
“…While initial experiments showed that CCBs did not improve renal survival in rats with subtotal nephrectomy [3, 4], it has been reported recently that both CCBs and ACE inhibitiors attenuate glomerular injury in subtotally nephrectomized rats [5]as well as in uninephrectomized spontaneously hypertensive rats [6]. CCBs have been shown to attenuate a deterioration in renal function and to reduce proteinuria in patients with nondiabetic renal insufficiency [7]and in those with diabetic nephropathy [8].…”
Section: Introductionmentioning
confidence: 99%